Arne Naess's Thoughts on Environmental Ethics in Islamic Perspective - Umam, Khoirul; Jakiyudin, Ahmad Havid; Hidayat, Muhammad Sofian; Roslan, Isma Aulia (KALAM, 2024)
Environmental ethics from deep ecology theory by Arne Naess is seen as giving a lot of attention to environmental issues and the sustainability of life. This theory is used as an alternative to view the world to improve the relationship between humans and their environment, namely the cultivation of environmental ethics. The environmental ethical principles offered by Naess are considered to be the basis for finding appropriate solutions to various environmental problems. It is very interesting to draw coherence between the deep ecology environmental ethical theory from an Islamic perspective, considering that in a complex manner, the principles of environmental conservation are contained in Islamic teachings. The purpose of this study is to explore the principles of environmental ethics in Arne Naess' deep ecology theory and to draw their coherence from an Islamic perspective. The philosophical hermeneutical method is used as an approach to interpreting the theory in an Islamic view. The results of the study show that Arne Naess' deep ecology principles can be mapped into three parts, namely: ecosophy, ecopolitics, and lifestyle. Arne Naess' deep ecology approach consists of ecocentrism and biocentrism theory approaches that emphasize the human view of respecting nature as a whole. However, from an Islamic perspective, not all humans have to be addressed to nature, as is the case with Arne Naess' deep ecology theory